The Motif of Hope in African American Preaching During Slavery and the Post-Civil War Era: There's a Bright Side Somewhere - Croft, Wayne E. (Lexington Books, 2017)
The Motif of Hope in African American Preaching during Slavery and the Post-Civil War Era: There's a Bright Side Somewhere explores the use of the motif of hope within African American preaching during slavery (1803–1865) and the post-Civil War era (1865–1896). It discusses the presentation of the motif of hope in African American preaching from an historical perspective and how this motif changed while in some instances remained the same with the changing of its historical context. Furthermore, this discussion illuminates a reality that hope has been a theme of importance throughout the history of African American preaching.